Species richness and distribution of lycophytes and ferns according to vegetation types in Sierra Norte de Puebla, Mexico - Tzompa-Coatl, Rosalía; Cerón-Carpio, Amparo B; Mendoza-Ruiz, Aniceto; Ceja-Romero, Jacqueline (Instituto de Ecología, A.C., 2022)
Background and Aims: In the Sierra Norte de Puebla (SNP), Mexico, the montane cloud forest is the vegetation with the greatest number of pteridophytes in the country; nevertheless, this region still lacks studies about the richness of this plant group. The objective of this work was to present a floristic list of the lycophytes and ferns of the SNP and determine the species affinity between the different vegetation types.Methods: Herbarium specimens from 1900 to 2018 were examined, including collections made by the authors. The species accumulation curve was calculated by nonparametric indices; the taxonomic biodiversity index (IB, taxa/km2) was estimated using results from this study and others from areas adjacent to SNP; the Sorensen similarity index (IS) was calculated, and a cluster analysis was performed to determine the species affinity between the vegetations. The conservation status of the taxa was also documented.Key results: In total 253 species, 12 varieties and one hybrid were recorded, all circumscribed in 81 genera and 29 families; 44 taxa had not been reported previously for this area, 14 of these are new records for the state of Puebla. The montane cloud forest had the highest richness (190 species and 10 varieties). The IB for the SNP was 30.4 taxa/km2. The completeness analysis showed a trend toward the asymptote, which indicates that the number of species could still increase (22-33%). Pteridophyte similarity between vegetation types was low (IS=0-0.52), the highest value was between medium evergreen and semi- deciduous forests.Conclusions: The SNP contains 69.8 % of pteridophytes of the state of Puebla, therefore it is imperative to implement conservation projects and to increase collections in the less explored municipalities, especially in those with montane cloud forests.